2017
DOI: 10.1016/j.jvs.2016.12.129
|View full text |Cite
|
Sign up to set email alerts
|

Off-the-shelf multibranched endograft for urgent endovascular repair of thoracoabdominal aortic aneurysms

Abstract: The off-the-shelf multibranched endograft is a safe and effective therapeutic option for urgent total endovascular TAAA repair for which a custom-made endograft is not obtainable in due time. However, the complex anatomy of these aneurysms needs a number of adjunctive and complex intraoperative procedures to achieve a durable repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 34 publications
5
65
0
Order By: Relevance
“…Technical success in this study was encouraging. Overall mortality #30 days (4%) was in line with other published series dedicated to the t-Branch device (range, 0%-6%) [14][15][16] despite the majority of patients electively treated in these studies. The outcome was also lower than in other CSG cohorts (range, 7%-11.6%).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Technical success in this study was encouraging. Overall mortality #30 days (4%) was in line with other published series dedicated to the t-Branch device (range, 0%-6%) [14][15][16] despite the majority of patients electively treated in these studies. The outcome was also lower than in other CSG cohorts (range, 7%-11.6%).…”
Section: Discussionsupporting
confidence: 87%
“…As noted previously, 16,28 the fixed length of the Zenith t-Branch device determines a higher coverage of the nondiseased aorta compared with the CSG and may determine a higher risk, especially in short extended disease. The authors agree with the suggested modifications designed to reduce proximal sealing and to increase the proximal diameter.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations